2019
DOI: 10.1111/1440-1681.13125
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐33a‐5p suppresses colorectal cancer cell growth by inhibiting MTHFD2

Abstract: Colorectal cancer (CRC) is one of the most common malignancies with high levels of invasiveness, drug resistance and mortality, but the internal mechanisms of CRC are largely unknown. MicroRNAs (miRs) have been reported to be involved in the development of CRC, and numerous studies have demonstrated that the abnormal expression of miR‐33a‐5p might be associated with CRC. However, the function and downstream mechanism of miR‐33a‐5p in colorectal cancer (CRC) remains unclear. Methylenetetrahydrofolate dehydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 26 publications
(30 reference statements)
0
26
0
Order By: Relevance
“…14 Yan et al revealed that miR-33a-5p repressed cell proliferation and migratory abilities in colorectal cancer. 30 Besides, miR-33a-5p was demonstrated to suppress cell proliferation and metastasis in hepatocellular carcinoma. 31 In consistent with their finding, our results explained miR-33a-5p overexpression abolished the effects of circ_ASAP2 on GC progression, and this meant that miR-33a-5p inhibited GC progression.…”
Section: Discussionmentioning
confidence: 99%
“…14 Yan et al revealed that miR-33a-5p repressed cell proliferation and migratory abilities in colorectal cancer. 30 Besides, miR-33a-5p was demonstrated to suppress cell proliferation and metastasis in hepatocellular carcinoma. 31 In consistent with their finding, our results explained miR-33a-5p overexpression abolished the effects of circ_ASAP2 on GC progression, and this meant that miR-33a-5p inhibited GC progression.…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancer, MTHFD2 expression promotes cancer cell growth, and MTHFD2 is targeted by miR-33a-5p, a microRNA with a major role in tumorigenesis. [ 32 ] In addition, miR-92a inhibits cancer cell proliferation and induces apoptosis by regulating MTHFD2 in acute myeloid leukemia. [ 33 ] Similarly, miR-9 can directly target MTHFD2 to exert anti-proliferative and pro-apoptotic effects in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et, al suggested that microRNA-940 could inhibit glioma progression by blocking mitochondrial folate metabolism through targeting of MTHFD2 [31]. Yam et, al indicated that microRNA-33a-5p suppresses the growth and migration of colorectal cancer cell by inhibiting MTHFD2 [32]. Li et, al reported that upregulation of miR-504-3p is associated with favorable prognosis of acute myeloid leukemia and may serve as a tumor suppressor by targeting MTHFD2 [33].…”
Section: Discussionmentioning
confidence: 99%